Do institutional pressures impact voluntary environment information disclosure? - Fan, Jing; Muhamad, Haslinah; Mohd Said, Ridzwana; Daud, Zaidi Mat (Centre for Research on Islamic Banking and Finance and Business, 2024)
Over the past decades, China's rapid economic growth has mainly come at the expense of excessive energy consumption, resulting in significant carbon dioxide emissions and other environmental challenges. China has pledged to peak its carbon emissions by 2030 to address the rising emissions, aiming for near-zero carbon neutrality by 2060. In this context, the legitimacy of institutions is essential, as it sheds light on the various effects of institutional pressures on organizational strategies and behaviors. Companies are increasingly improving their voluntary disclosure of environmental information to maintain legitimacy. However, many companies still need to determine whether the public and stakeholders value their environmental and social performance. Managers often believe that the costs of voluntary disclosure outweigh the benefits. This study analyzes how institutional pressures— coercive, normative, and mimetic pressure—affect voluntary environmental information disclosure in China. We gathered survey responses from managers at 93 listed manufacturing companies based in China. A cross-sectional quantitative approach was utilized, with data collection occurring between March and May 2024. We employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to investigate the impact of institutional pressures on the voluntary disclosure of environmental information. The findings suggest that coercive and normative pressures significantly enhance voluntary environmental information disclosure, whereas mimetic pressure shows no significant effect. These findings indicate that voluntary environmental information disclosure in China remains underdeveloped and lacks a clear industry framework. As a result, companies are increasingly prioritizing compliance with regulatory standards and actively engaging with stakeholders rather than simply imitating the behaviors of their peers.